Comparative phylogenomic and structural analysis of canonical secretory PLA2 and novel PLA2-like family in plants - Ankush Ashok Saddhe; Martin Potocký; Martin Potocký (Frontiers in Plant Science, 2023)
Plant secretory phospholipase A2 (sPLA2) is a family of lipolytic enzymes involved in the sn-2 hydrolysis of phospholipid carboxyester bonds, characterized by the presence of a conserved PA2c domain. PLA2 produces free fatty acids and lysophospholipids, which regulate several physiological functions, including lipid metabolism, plant growth and development, signal transduction, and response to various environmental stresses. In the present work, we have performed a comparative analysis of PA2c domain-containing genes across plants, focusing on gene distribution, phylogenetic analysis, tissue-specific expression, and homology modeling. Our data revealed the widespread occurrence of multiple sPLA2 in most land plants and documented single sPLA2 in multiple algal groups, indicating an ancestral origin of sPLA2. We described a novel PA2c-containing gene family present in all plant lineages and lacking secretory peptide, which we termed PLA2-like. Phylogenetic analysis revealed two independent clades in canonical sPLA2 genes referred to as α and β clades, whereas PLA2-like genes clustered independently as a third clade. Further, we have explored clade-specific gene expressions showing that while all three clades were expressed in vegetative and reproductive tissues, only sPLA2-β and PLA2-like members were expressed in the pollen and pollen tube. To get insight into the conservation of the gene regulatory network of sPLA2 and PLA2-like genes, we have analyzed the occurrence of various cis-acting promoter elements across the plant kingdom. The comparative 3D structure analysis revealed conserved and unique features within the PA2c domain for the three clades. Overall, this study will help to understand the evolutionary significance of the PA2c family and lay the foundation for future sPLA2 and PLA2-like characterization in plants.